Diffusion-weighted MRI for Early Prediction of Treatment Response on Preoperative Chemoradiotherapy for Patients With Locally Advanced Rectal Cancer: A Feasibility Study. Issue 3 (March 2016) - Jacobs, Lotte; Intven, Martijn; van Lelyveld, Niels; Philippens, Marielle; Burbach, Maarten; Seldenrijk, Kees; Los, Maartje; Reerink, Onne
Abstract : Objective: This study investigates the predictive value of diffusion-weighted magnetic resonance imaging (DW-MRI) for good pathological response at different time points during and after preoperative chemoradiotherapy (CRT) in locally advanced rectal cancer. Background: Preoperative CRT followed by total mesorectal excision (TME) is the standard of care for locally advanced rectal cancer. The use of standard radical surgery in good treatment responders after CRT is being questioned. Methods: Patients with locally advanced rectal adenocarcinoma were treated with preoperative CRT followed by surgery. DW-MRI scans were performed before CRT, during the third week of CRT, 4 weeks post-CRT and presurgery. Tumor apparent diffusion coefficient (ADC) values were acquired from the DW-MRI scans. After surgery the pathological tumor regression grade was assessed according to the classification by Mandard et al [Cancer. 1994;73:2680–2686]. Patients with pathological complete or near-complete response (tumor regression grade 1–2) were classified as good responders (GRs). Results: Twenty-two patients participated of which 9 were GRs (41%). Pre-CRT ADC values were lower in good versus moderate/poor responders ( P = 0.04). ADC values during CRT and four weeks post-CRT were higher in GR. ADC values presurgery did not differ between response groups. For all time points the relative ADC increase (ΔADC) compared to the ADC pre-CRT was higher in GR ( P < 0.001). The ΔADC during CRT and four weeks post-CRT were the best predictive parameters for pathological good response. Conclusions: This study shows that DW-MRI is feasible to select good treatment responders during preoperative CRT for locally advanced rectal cancer.